relSCAN - A system for extracting chemical-induced disease relation from biomedical literature - Onye, Stanley Chika; Akkeles, Arif; Dimililer, Nazife (Academic Press Inc Elsevier Science, 2018)
This paper proposes an effective and robust approach for Chemical-Induced Disease (CID) relation extraction from PubMed articles. The study was performed on the Chemical Disease Relation (CDR) task of BioCreative V track-3 corpus. The proposed system, named re1SCAN, is an efficient CID relation extraction system with two phases to classify relation instances from the Co-occurrence and Non-Co-occurrence mention levels. We describe the case of chemical and disease mentions that occur in the same sentence as 'Co-occurrence', or as 'Non-Co-occurrence' otherwise. In the first phase, the relation instances are constructed on both mention levels. In the second phase, we employ a hybrid feature set to classify the relation instances at both of these mention levels using the combination of two Machine Learning (ML) classifiers (Support Vector Machine (SVM) and J48 Decision tree). This system is entirely corpus dependent and does not rely on information from external resources in order to boost its performance. We achieved good results, which are comparable with the other state-of-the-art CID relation extraction systems on the BioCreative V corpus. Furthermore, our system achieves the best performance on the Non-Co-occurrence mention level.
Keywords: Chemical disease relation; Chemical-induced diseases; Relation extraction; Classifier ensemble; SVM, J48 decision tree